Bridging the Gap From Screening Assays to Estrogenic Effects in Fish: Potential Roles of Multiple Estrogen Receptor Subtypes - Yost, Erin E. (American Chemical Society, 2014)
[Image: see text] This study seeks to delineate the ligand interactions that drive biomarker induction in fish exposed to estrogenic pollutants and provide a case study on the capacity of human (h) estrogen receptor (ER)-based in vitro screening assays to predict estrogenic effects in aquatic species. Adult male Japanese medaka (Oryzias latipes) were exposed to solutions of singular steroidal estrogens or to the estrogenic extract of an anaerobic swine waste lagoon. All exposure concentrations were calibrated to be equipotent based on the yeast estrogen screen (YES), which reports activation of hERα. These exposures elicited significantly different magnitudes of hepatic vitellogenin and choriogenin gene induction in the male medaka. Effects of the same YES-calibrated solutions in the T47D-KBluc assay, which reports activation of hERα and hERβ, generally recapitulated observations in medaka. Using competitive ligand binding assays, it was found that the magnitude of vitellogenin/choriogenin induction by different estrogenic ligands correlated positively with preferential binding affinity for medaka ERβ subtypes, which are highly expressed in male medaka liver prior to estrogen exposure. Results support emerging evidence that ERβ subtypes are critically involved in the teleost estrogenic response, with the ERα:ERβ ratio being of particular importance. Accordingly, incorporation of multiple ER subtypes into estrogen screening protocols may increase predictive value for the risk assessment of aquatic systems, including complex estrogenic mixtures.